ANALISIS HUBUNGAN PENGGUNAAN BAHASA NONBAKU DAN SENTIMEN KOMENTAR YOUTUBE PADA KASUS KECURANGAN SAAT UTBK - Azzahra, Amalia; Pratiwi, Salwa Risda; Lubis, Wulan Fransiska; Floren Green Chia; S. Garingging, Veronika Valentin; Simanjuntak, Elvi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the use of non-standard language in YouTube comment sections regarding cheating during Computer-Based Written Exams and its relationship to public sentimen in the comments. The study aims to identify the forms of non-standard language use and the relationship between the number of non-standard words and comment sentimen. The research method used is quantitative descriptive with a sociolinguistic approach. The research data consists of 390 YouTube comments obtained through automated data collection techniques. Analysis was conducted through the stages of data preprocessing, identification of non-standard words, sentimen analysis, calculating the frequency of non-standard word occurrences, creating a cross-tabulation table, and a chi-square test. The results of the study indicate that negative sentimen has the highest usage of non-standard words, with a chi-square test result of 0.000024, indicating a significant relationship between the use of non-standard words and public sentimen in social media comments. Keywords: Sentimen Analysis, Non-Standard Language, UTBK, YouTube